Penyuluhan Kesehatan Remaja: Langkah-Langkah Pencegahan Anemia Di Kalangan Siswa SMP Negeri 3 Makassar - Ratnah, St (Jurnal Pengabdian Kefarmasian, 2024)
Teenager Health Counseling: Measures to Prevent Anemia Among Students of SMP Negeri 3 MakassarAnemia, particularly among adolescents, is a significant public health issue in Indonesia. Adolescent girls are more vulnerable to anemia due to menstruation and unbalanced diets. In South Sulawesi, the prevalence of anemia among adolescent girls reaches 33.7%, highlighting the need for preventive measures. Considering its impact on quality of life and academic performance, it is crucial to provide education on anemia prevention to adolescents, especially in schools. Activity Objective: The primary goal of this activity is to increase students' knowledge about anemia by providing comprehensive information to 9th-grade students. This includes covering the causes, symptoms, and prevention of anemia. It is expected that students will gain a better understanding of blood health and the role of iron in preventing anemia. Additionally, the activity aims to raise awareness about the importance of a healthy diet through educating students on the role of balanced nutrition, particularly iron intake, in maintaining good health and preventing anemia. Methodology: The method used in this outreach is a health counseling session, designed to present clear and easily understandable information about anemia prevention through educational and interactive materials. The activity was conducted in collaboration with the principal of SMP Negeri 3 Makassar, while the target participants were 9th-grade students at the school in Makassar. The expected output of this activity is a scientific article. Conclusion: The activity resulted in a 77.14% increase in the target group's knowledge regarding anemia and its prevention. Anemia, terutama di kalangan remaja, merupakan masalah kesehatan yang signifikan di Indonesia. Remaja putri lebih rentan terhadap anemia akibat menstruasi dan pola makan yang kurang seimbang. Di Sulawesi Selatan, angka prevalensi anemia pada remaja putri mencapai 33,7%, yang menunjukkan perlunya langkah-langkah pencegahan. Mengingat dampaknya terhadap kualitas hidup dan prestasi akademik, penting untuk memberikan edukasi tentang pencegahan anemia kepada remaja, terutama di sekolah-sekolah. Tujuan Kegiatan: meningkatkan pengetahuan siswa tentang anemia dengan memberikan informasi yang komprehensif kepada siswa, khususnya kelas IX, mengenai anemia, termasuk penyebab, gejala, serta cara pencegahannya. Diharapkan siswa akan lebih memahami pentingnya kesehatan darah dan peran zat besi dalam mencegah anemia. Serta membangun kesadaran akan pentingnya pola makan sehat  melalui edukasi siswa mengenai pentingnya gizi seimbang, terutama asupan zat besi, dalam menjaga kesehatan tubuh dan mencegah anemia. Metode kegiatan Metode yang digunakan dalam penyuluhan ini adalah penyuluhan, yang dirancang untuk memberikan informasi yang jelas dan mudah dipahami tentang pencegahan anemia melalui materi edukatif dan interaktif.. Mitra pelaksana adalah Kepala Sekolah SMP Negeri 3 Makassar dan mitra sasaran adalah siswa kelas IX SMP Negeri 3 Makassar, Kota Makassar. Capaian luaran adalah artikel ilmiah. Kesimpulan yang diperoleh terjadi peningkatan pengetahuan mitra sasaran mengenai anemia dan cara pencegahannya sebesar 77,14%.